Phytochemical screening and gc - ms analysis of methanolic extract of leaves of Pisonia aculeata linn - S.PRIYA,; A.SUBHASHINI, (International Journal of Pharma and Bio Sciences, 2016)
Plants have been a major source of therapeutic agents since time immemorial. Plants have the ability to synthesize a wide variety of chemical compounds with important biological functions. Pisonia aculeata , an armed scandent shrub or small tree belongs to the family Nyctaginaceae. The leaves and barks are used by the tribes and native medical practitioners to treat various ailments. The present study was carried out to screen the phytochemicals present in the leaves of Pisonia aculeata and further analysis of components present in it by GC- MS analysis. Eighteen compounds were identified. The major constituents are Thiopene tetrahydro-2-methyl, n-Hexadecanoic acid, Sulphuric acid dimethyl ester, Phytol, 9,12,15-Octadecatrienoic acid. Mass Spectra of the compounds was matched with National Institute of Standards and Technology (NIST) Library. These different active phytocompounds have been found to possess a wide range of activities which may help in the protection against various diseases. This analysis forms a basis for the biological characterization and importance of the compounds identified.